NILAI – NILAI PENDIDIKAN AGAMA HINDU DALAM PETULANGAN SADDULA PADA UPACARA PENGABENAN DI BANJAR PAKETAN KELURAHAN PAKET AGUNG KECAMATAN BULELENG KABUPATEN BULELENG - Komang Geri Arnata (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
The beliefs embraced by Hindus in the procession of returning the elements of human formation (Panca Maha Bhuta) to the creator must be by means of a vehicle or vehicle. The rides referred to at the Ngaben ceremony procession are referred to as Petrepans. Generally it can be interpreted as a means or vehicle used at the Ngaben ceremony and is believed to be able to deliver and give way to the spirits of people who have died. Based on the background above, there are three problems, namely: 1) What is the form of Saddula's Repetition used at the ceremony of obedience? 2) What is the community's perception of the use of Saddula's Repayment at the ceremonial ceremony? 3) What are the values of Hindu religious education contained in the use of Saddula's Repayment at the ceremonial ceremony? The results of research that has been carried out is Saddula's Repetition form consists of six animal elements, namely: dragon, lion, pig, eagle, fish and cow. So that raises public perceptions that the word Saddula means six colors or types of animals that are used to form a unique Repetition type based on aesthetic values, social solidarity and ethical values, so that it can be concluded that diversity arises which can be used as a kufr without producing a conflict.Keywords: Saddula Repayment, Ceremonial Ceremony